Enhancing STEM Education through IoT-Based Distance Monitoring Projects in High Schools - Istiqomah Istiqomah; Khilda Afifah; Porman Pangaribuan; Teguh Patriananda; Ni Kadek Cindy Sriastiti; Justin Fairman Tan; Tsania Puspa Kirana; Garry Nelson (FOUNDAE (Foundation of Advanced Education), 2026)
This community service program was conducted in response to the demands of the Fourth Industrial Revolution, which requires stronger digital literacy and practical STEM competencies in schools. The program aimed to introduce IoT-based STEM learning to teachers and students at Situraja State Senior High School (SMAN Situraja), a rural school in West Java, Indonesia, to enhance digital literacy and promote hands-on STEM education. To achieve this, the program implemented an IoT-based distance monitoring project using an ultrasonic sensor, an ESP32 microcontroller, and the Blynk platform through a project-based learning approach that included lectures, collaborative practical sessions, and interactive feedback activities. The program was evaluated using post-activity questionnaires administered to both teachers and students to capture their perceptions of the learning activities and outcomes. The results showed highly positive teacher responses, with 75–100% of participants selecting